International diversification and cryptocurrencies: an ASEAN-5 perspective - Madhavan, Keerthan (2023)
The purpose of this research is to investigate the potential advantages of diversifying international investment portfolios by integrating key cryptocurrencies across the equities and fixed income markets of the ASEAN-5 countries. Furthermore, the purpose of this research is to investigate the co-movements between equity indices, fixed income indices, and cryptocurrency value trends in order to evaluate the benefits of diversification offered by this asset class. This will be done by analysing the risk-reward tradeoff from the perspective of a portfolio optimization strategy using data ranging from October 2018 to December 2022. According to the findings of this study, the addition of cryptocurrencies to a diversified portfolio comprising ASEAN-5 stocks and fixed income results in increased risk-adjusted returns for each of the corresponding portfolio designs. This increase is shown by an increase in the Sharpe ratio. The research also demonstrates the relationship that exists between cryptocurrencies and indexes of equities and fixed income markets.